2010
DOI: 10.1002/mar.20328
|View full text |Cite
|
Sign up to set email alerts
|

Children's brand symbolism understanding: Links to theory of mind and executive functioning

Abstract: Against a background of research suggesting that brand symbolism understanding does not develop until 7 to 11 years of age, two studies investigate various aspects of preschool children's brand knowledge. While children's recognition of child-oriented brands is found to be significantly greater than their recognition of brands that are marketed primarily to teens and adults, these young children do recognize brands. In a second study, children's ability to form mental representations of brands is assessed, alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
91
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(102 citation statements)
references
References 23 publications
(55 reference statements)
6
91
0
5
Order By: Relevance
“…Several studies have demonstrated that teenagers also attach particular importance to brand symbolism and use it to communicate their identities (Chaplin & John, 2005;Escalas & Bettman, 2005;Grant & Stephen, 2006;Ohl, 2003). For instance, U.S. research revealed that many children have the ability to recognize brands by the age of 3 (e.g., McAlister & Cornwell, 2010). Thus, by the time children reach 11 or 12 years of age, they become very familiar with branded products.…”
Section: H9mentioning
confidence: 96%
“…Several studies have demonstrated that teenagers also attach particular importance to brand symbolism and use it to communicate their identities (Chaplin & John, 2005;Escalas & Bettman, 2005;Grant & Stephen, 2006;Ohl, 2003). For instance, U.S. research revealed that many children have the ability to recognize brands by the age of 3 (e.g., McAlister & Cornwell, 2010). Thus, by the time children reach 11 or 12 years of age, they become very familiar with branded products.…”
Section: H9mentioning
confidence: 96%
“…Also using theory of mind, McAlister and Cornwell (2010) have shown that preschoolers are capable of recognizing brand names and understanding them as social symbols. Similarly, extant literature on preschoolers' persuasion knowledge argues that most preschoolers can recognize brands (McAlister & Cornwell, 2010) and advertising, but are unaware that ads can be misleading, biased, and self-serving (e.g., Levin, Petros, & Petrella, 1982).…”
Section: Models Of Consumer Socialization and The Very Youngmentioning
confidence: 99%
“…In order to quantify how much information a child has processed and stored about food brands, we utilized a recently developed "brand representation task" by McAlister and Cornwell (2010). While collage-type tasks have been used to assess constructs such as materialism in children and adolescents (Chaplin & John, 2005, 2007, across marketing, psychology, sociology and health literatures, this was the only brand knowledge task for children this age that could be identified.…”
Section: 13 Nsmentioning
confidence: 99%